To Maurice Harmon, 5 October 2017 - Murray, Christopher (ABEI Journal, 2017)
Speech at University College Dublin, School of English, Drama and Film, paying tribute to Maurice Harmon on the occasion of his book donationto the Special Collections Reading Room.